Efeitos do tipo de sistema adesivo e região do dente sobre a resistência adesiva à dentina - Melo, Renata Marques de [UNESP] (2005)
This study aimed to evaluate lhe bond strengths between two total etching adhesive systems and (two and three steps) anda self-etching system to coronal and root canal dentin. The root canal of thirty human anterior teeth were endodontically instrumented and prepared with specific burs. Aestheti Plus #2 posts were duplicated in dual resin cement (Duo-link) and three groups (n=10) were formed, according to the adhesive sysfem used: 3 steps total etching adhesive system (3TE) - All-Bond 2 + resin cement post (rcp) + Duo-link (DI); 2 steps total etching adhesive system (2TE) - One-Step Plus + rcp + DI; sef-etching system (SE) Tyrian/One-Step Plus + rcp +DI. Following cementation, the teeth were cut transversally in eight sections (1,5mm), from the CEJ to 4mm above the canal apex. The sections were subjected to the push-out test in a universal testing machine (1mm.min-1). The data of bond strength were statistically analyzed with 2-way Anova of repeated measures (α<0.05), which showed that the interaction effect was significant. This meant that the relationship between the adhesives was not the same depending on the tooth region. Regarding the adhesive factor'' the comparison of means with Tukey test (α<0.05) showed that 3TE (mean ± standard deviation: 5,22 ± 1,70) was statistically superior to 2TE (2,60 ± 1,74) and SE (1,68 ± 1,85). Under the conditions of the present study, the three step total etching system had the highest bond strengths to dentin, especially in the coronal region